PS02.075: USEFULNESS OF FDG-PET TO DECIDE THE INDICATION FOR ENDOSCOPIC RESECTION FOR SUPERFICIAL ESOPHAGEAL CANCER. (14th September 2018) - Nakajima, Masanobu; Muroi, Hiroto; Kikuchi, Maiko; Tani, Yukiko; Yamaguchi, Satoru; Sasaki, Kinro
Abstract: Background: 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) is a useful imaging modality to reflect the tumor activity. However, FDG-PET is mainly used for advanced cancer rather than superficial cancer. In this study, we investigate the relationship between the superficial tumor depth of esophageal cancer and FDG uptake, and discuss the possibility of using FDG-PET in making the decision for performing endoscopic resection. Methods: From 2009 to 2017, 444 esophageal cancer patients underwent esophagectomy or Endoscopic submucosal dissection (ESD), and 195 were diagnosed with pathological superficial cancer. Among them, 146 patients were examined by FDG-PET before esophagectomy or ESD. For these 146 patients, the relationship between pathological tumor depth and FDG uptake was analyzed. Results: Mean maximun standardized uptake value (SUV Max) in pT1a-EP/LPM was 1.362 ± 0.890, pT1a-MM/pT1b-SM1 was 2.453 ± 1.872, and pT1b-SM2/SM3 was 4.265 ± 3.233 ( P  < 0.0001). Among 51 pT1a-EP/LPM tumors, 10 (19.6%) showed positive detection of FDG. For pT1a-MM/pT1b-SM1 and pT1b-SM2/SM3, the detection rates were 52.9% (18/34) and 82.0% (50/61), respectively. The detection rate for pT1a-EP/LPM was significantly lower than for the other two groups ( P  < 0.0001). Among 10 FDG-PET positive patients, the reason for one lesionbeing PET positive could not be determined; however, nine of ten lesions had suitable reasons for the lesions being detected by PET and thus not being ER indication. PET diagnosis tends to be more accurate than endoscopic diagnosis ( P = 0.0574) Conclusion: Negative detection of superficial esophageal sqamous cell carcinoma by FGD-PET is useful for deciding the indication for ER. Furthermore, when FDG uptake is recognized, a therapeutic modality other than ER should be considered. Disclosure: All authors have declared no conflicts of interest.